Analisis Semiotika terhadap Simbolisme Gaya Eropa dan Tropis pada Arsitektur Istana Bogor - Suhendro Suhendro; Dara Wisdianti (PT. Arsil Reka Engineering, 2024)
This research examines Bogor Palace as an architectural text that represents a fusion of European and tropical styles through a semiotic approach. Bogor Palace is not only a symbol of Dutch colonial power but also reflects the adaptation of Indonesian culture and tropical environment. This research aims to reveal the meanings and symbols contained in the architectural elements of Bogor Palace, such as symmetrical facades, tall pillars, large windows, cross ventilation, and steep roofs. Using semiotic methods, this research analyzes how these elements function as signs that represent aesthetic, historical and ecological values. The results show that the European architectural style of Bogor Palace, reflected through classical structures such as pillars and decorative ornaments, symbolizes the status of power and the influence of colonial culture. On the other hand, tropical elements such as cross ventilation, spacious terraces, and steep roofs represent adaptation to local environmental conditions, while symbolizing harmony between humans and nature. The symbolism in this design not only serves to fulfill functional needs, but also creates a visual narrative that reflects the dialog between foreign and local cultures. The study concludes that Bogor Palace is an artifact rich in semiotic meaning, where each architectural element contains messages about history, culture and ecological adaptation. This research contributes to the study of colonial architecture, particularly in understanding how historic buildings can be interpreted as sign systems that represent cultural and environmental complexities.